2009
DOI: 10.1002/cphc.200800815
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Structures of Self‐Assembled Gold Nanoparticles as a Unique SERS and SEIRA Substrate

Abstract: Metallic multilayer structures consisting of self-assembled nanoparticles are prepared by successive immersion of a functionalized glass substrate in a gold colloidal suspension, and are characterized by UV/Vis spectroscopy and atomic force microscopy. The ability of the thin film to concomitantly enhance the Raman and IR signals of an adsorbed molecule is evaluated and a detailed analysis of the recorded spectra is provided, which emphasizes the capability of these complementary methods to provide information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 44 publications
(43 reference statements)
0
25
0
Order By: Relevance
“…12 To date, substrates capable of simultaneously enhancing Raman and IR signals were demonstrated for silver nanorod arrays, 13 gold thin-film electrodes, 14 gold nanoshell arrays 15 and multilayer structures of self-assembled gold nanospheres. 16 In the present study, this was shown for the first time using in-situ prepared gold nanostars (AuNSts). Two mechanisms predominantly contribute to the enhancement observed both in SEIRAS and SERS, namely electromagnetic enhancement due to the high electric field strength surrounding the nanoparticles, and chemical enhancement resulting from chemical interactions between the analyte and the nanoparticles.…”
Section: Introductionmentioning
confidence: 68%
“…12 To date, substrates capable of simultaneously enhancing Raman and IR signals were demonstrated for silver nanorod arrays, 13 gold thin-film electrodes, 14 gold nanoshell arrays 15 and multilayer structures of self-assembled gold nanospheres. 16 In the present study, this was shown for the first time using in-situ prepared gold nanostars (AuNSts). Two mechanisms predominantly contribute to the enhancement observed both in SEIRAS and SERS, namely electromagnetic enhancement due to the high electric field strength surrounding the nanoparticles, and chemical enhancement resulting from chemical interactions between the analyte and the nanoparticles.…”
Section: Introductionmentioning
confidence: 68%
“…54 Slight intensity modification and frequency shifts in the nanovector spectrum with respect to the bulk are ascribed to the gold Np surface enhanced infrared absorption effect. 55 Titration experiments using the Coomassie Brilliant Blue (CBB) dye allowed for a quantitative estimation of the number of folate molecules bound to the single Np. 56 The result shows an average number of 1900 ± 200 folate molecules (see section S3 of the ESI †).…”
Section: Nanovector Preparation and Characterizationmentioning
confidence: 99%
“…Although successful in desirable high‐resolution features, these routes usually rely heavily on a sophisticated and costly instrument and are unfortunately encumbered with several fundamental limitations, such as difficulty in fabrication of stacked 3D structures and compromised spatial resolution at approximately 10 nm. Relative the to top‐down approach, many wet‐chemistry methods have been extensively utilized in the fabrication of large‐scale 3D SERS‐active substrate, like metal cylindrical nanotubes, conical nanotubes, nanoparticles, and nanowires, presenting the promising results in transforming SERS to routine chemical analysis in research lab and in fieldwork outside . Further chemical modification and metallization on cellulose network reinvigorates this foldable device to many novel functions and applications, propelling it to another dimension to the potential of disposable devices for advanced diagnostics and therapeutics in clinic trial and environmental monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Relative the to top-down approach, many wet-chemistry methods have been extensively utilized in the fabrication of large-scale 3D SERS-active substrate, like metal cylindrical nanotubes, conical nanotubes, nanoparticles, and nanowires, presenting the promising results in transforming SERS to routine chemical analysis in research lab and in fieldwork outside. [26][27][28] Further chemical modification and metallization on cellulose network reinvigorates this foldable device to many novel functions and applications, propelling it to another dimension to the potential of disposable devices for advanced diagnostics and therapeutics in clinic trial and environmental monitoring. Here we report a SERS approach on Ag-embedded chromatograph paper prepared by electroless deposition, which reinforces the ability of chemical identification and analysis without extra labeling or plugging to high voltage supply.…”
Section: Introductionmentioning
confidence: 99%